2015
DOI: 10.1016/j.jvs.2014.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Celiac Artery Decompression for Median Arcuate Ligament Syndrome: A United States National Inpatient Sample Study

Abstract: requiring dialysis, colonic ischemia requiring resection, limb ischemia requiring amputation, multisystem organ failure, or death. Endoleaks were classified in accordance with the standardized reporting practices of the Society for Vascular Surgery. Results: A total of 391 patients with complete family history and clinical data underwent elective AAA repair from 2004 to 2014. Demographics were consistent with a standard AAA population and did not differ between fAAA and spAAA patients. Sixty-two percent (n ¼ 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Although the true incidence of the disease is unknown, Rezigh et al reported 33,951 cases of MALS were diagnosed in a 12 year period using the Nationwide Inpatient Sample [ 2 ]. Interestingly, in their study only 2.4% of all cases identified had undergone surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the true incidence of the disease is unknown, Rezigh et al reported 33,951 cases of MALS were diagnosed in a 12 year period using the Nationwide Inpatient Sample [ 2 ]. Interestingly, in their study only 2.4% of all cases identified had undergone surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Median arcuate ligament syndrome (MALS) is defined as a symptomatic extrinsic compression of the celiac axis caused by the median arcuate ligament (MAL) [ 1 ]. Often considered a rare entity, more recently a study using the Nationwide Inpatient Sample showed an increasing number of patients with this diagnosis [ 2 ]. There remains controversy regarding this diagnosis and its epidemiology, as celiac axis compression by the MAL can be found incidentally in up to 7.3% of patients who received cross-sectional abdominal imaging for other reasons [ 1 , 3 ].…”
mentioning
confidence: 99%
“…Those who had CAD had much lower rates of comorbidities, with hypertension being the highest prevalence at 22.4% and the rest ranging from zero percent to 14%. Researchers of this study [ 23 ] asserted there is a need to educate physicians about these benefits of CAD surgery for patients with MALS. The high rates of comorbidities with MALS in this study [ 23 ] also showcases the extensive impact MALS has on multiple body systems.…”
Section: Literature Review - Interprofessional Management Of Median Amentioning
confidence: 99%
“…Researchers of this study [ 23 ] asserted there is a need to educate physicians about these benefits of CAD surgery for patients with MALS. The high rates of comorbidities with MALS in this study [ 23 ] also showcases the extensive impact MALS has on multiple body systems. Thus far, there are no rigorous quantitative studies or descriptive qualitative studies about interprofessional management strategies for MALS available in the literature.…”
Section: Literature Review - Interprofessional Management Of Median Amentioning
confidence: 99%
See 1 more Smart Citation